Management of Teacher Performance Appraisal in Madrasah - Juliana Juliana; Murniati Murniati; Bahrun Bahrun (AL-ISHLAH: Jurnal Pendidikan, 2022)
The low performance of teachers will impact the quality of student graduation, which in turn will also affect the achievement of educational goals. The quality in the learning process can be grouped into the quality of the input, the quality of the process and the quality of the learning output. The purpose of this study was to see planning teacher performance appraisals, strategies for implementing teacher performance appraisals, and supervision of teacher performance appraisal. Data collection techniques through observation, interviews, and documentation study. The subjects of this study are school principals, supervisors, and teachers at a Madrasah in Banda Aceh. Data analysis used data reduction, data presentation, drawing conclusions and verification. The results showed: (1) teacher performance was carried out by the authorities stipulated by the government, based on the stated performance appraisal, had been running according to four teacher competency standards including; pedagogical competence, social competence, personal competence, and professional competence (2) the strategy for implementing teacher performance assessments can be seen from the ability of teachers to carry out the teaching and learning process, namely: preparing learning plans, managing the class, using media or learning resources, understanding educational foundations, implementing BK program, carry out learning evaluation, (3) the purpose of supervising teacher performance by supervisors consists of principals and supervisors to determine the professional level of teachers in work and determine the teacher's availability of instruments. This supervision will improve the quality of education so that teachers will not underestimate the learning process.